FOOD SECURITY POLITICS AND ECONOMIC DIPLOMACY: KUNINGAN REGENCY’S SWEET POTATO PARADIPLOMACY IN THE GLOBAL NETWORK - Apriliani, Diah; Finaldin, Tom; Emelda, Salsabila Aulia (Universitas Padjadjaran, 2026)
This study analyzes the role of economic diplomacy in strengthening the global sweet potato network in Kuningan Regency from a political economy perspective. As the largest sweet potato producer in West Java with production of 108,496 tons in 2023, Kuningan has enormous potential that has not been optimally utilized for global network development. The research objectives are to analyze political dynamics in economic diplomacy implementation, identify political actors’ role in facilitating international market access, and formulate strategies for strengthening global networks. This research uses a qualitative approach with case study design, where data collection was conducted through in-depth interviews with three key informants: Head of Kuningan Regency Food Security and Agriculture Agency, Head of Cilimus Technical Implementation Unit, and Head of Cilimus Agricultural Extension Center, supplemented by document analysis of regional planning documents, production statistics, and policy materials. Data were analyzed using thematic analysis to identify patterns and themes related to economic diplomacy mechanisms and global network development. The study reveals weak global networks between Kuningan sweet potato producers and international markets, with only 2-3% of production absorbed by export markets despite significant price differentials (local market IDR 3,500-4,000/kg versus export IDR 15,000-20,000/kg). Indonesia has adequate economic diplomacy infrastructure with 19 Indonesian Trade Promotion Centers (ITPCs) and 24 trade attachés, but utilization for alternative food commodities remains limited with budget allocation below 5%. The findings demonstrate that successful sweet potato economic diplomacy requires a multi-level governance approach integrating regional political commitment, national policy coordination, and global strategic positioning. This study contributes to regional economic diplomacy theory development and provides strategic recommendations for local governments to leverage existing diplomatic infrastructure, strengthen multi-stakeholder collaboration, and position sweet potatoes as strategic export commodities within Indonesia’s broader agricultural diplomacy framework.